Nucleotide Oligomerization and Binding Domain 2-Dependent Dendritic Cell Activation Is Necessary for Innate Immunity and Optimal CD8(+) T Cell Responses to Influenza A Virus Infection - Lupfer, Christopher (American Society for Microbiology, 2014)
Nucleotide oligomerization and binding domain (NOD)-like receptors (NLRs) are important in the innate immune response to viral infection. Recent findings have implicated NLRP3, NOD2, and NLRX1 as important players in the innate antiviral response, but their roles in the generation of adaptive immunity to viruses are less clear. We demonstrate here that NOD2 is critical for both innate and adaptive immune responses necessary for controlling viral replication and survival during influenza A virus (IAV) infection. Nod2(−/−) mice have reduced beta interferon (IFN-β) levels and fewer activated dendritic cells (DCs), and the DCs are more prone to cell death in the lungs of Nod2(−/−) mice during IAV infection. In agreement with the role for DCs in priming adaptive immunity, the generation of virus-specific CD8(+) T cells and their activation and production of IFN-γ were lower in Nod2(−/−) mice. Furthermore, Nod2(−/−) DCs, when cocultured with T cells in vitro, have a lower costimulatory capacity. Thus, Nod2(−/−) DCs are unable to efficiently prime CD8(+) T cells. These findings demonstrate that Nod2 is critical for the generation of both innate and adaptive immune responses necessary for controlling IAV infection. IMPORTANCE The innate immune system is the host's first line of defense against invading pathogens and is also necessary for alerting and activating T and B cells to initiate the adaptive immune response. We demonstrate here that the innate immune receptor NOD2 is required for the production of antiviral type I interferons and the activation and survival of dendritic cells that, in turn, alert T cells to the presence of influenza A virus infection. In mice that are missing NOD2, interferon levels are lower, and the CD8(+) T cell response is impaired. As a result, the animals cannot control virus replication in their lungs as efficiently. This discovery helps us understand how the body naturally responds to virus infection and may help in the development of vaccines that use NOD2 to stimulate the CD8(+) T cell response, thus providing better protection against influenza A virus infection.